KEBAIKAN DAN KEBURUKAN MENURUT ZOROASTRIANISME (MENGENAL AJARAN MORAL ZARATHUSTRA) - Kholil, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Religions always have two values, which are very distinctive, i.e. the goodness and the badness. Al Quran describes these two qualities with various uslub related to Arabic culture: al hasanat and al sayyiâ€™at. The goodness and the badness are always â€œin a warâ€ until the end of the world. As religions, both Islam and Zoroaster rely on the faith toward God to edify their followers for performing the goodness and leaving the badness. This paper reviews to some extentâ€“some commonalities between the moral teachings of Islam and those of Zoroaster (excluding few shared concepts of theology and creation process of the first living man). Moslems are required to apply the concept of amar maâ€™ruf nahi munkar, while Zoroastrians are called to implement the four principles of moral attitude: putting the weapon down, ending any quarrel, exploring the independence, and performing good attitude.